2018
DOI: 10.1002/advs.201800360
|View full text |Cite
|
Sign up to set email alerts
|

3D Self‐Architectured Steam Electrode Enabled Efficient and Durable Hydrogen Production in a Proton‐Conducting Solid Oxide Electrolysis Cell at Temperatures Lower Than 600 °C

Abstract: Hydrogen production via water electrolysis using solid oxide electrolysis cells (SOECs) has attracted considerable attention because of its favorable thermodynamics and kinetics. It is considered as the most efficient and low‐cost option for hydrogen production from renewable energies. By using proton‐conducting electrolyte (H‐SOECs), the operating temperature can be reduced from beyond 800 to 600 °C or even lower due to its higher conductivity and lower activation energy. Technical barriers associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
83
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 56 publications
(46 reference statements)
1
83
0
Order By: Relevance
“…Figure c compares the electrolysis performance of our optimized cells with those of oxygen‐conducting SOECs reported in the literature . Some recent advances of electrolysis cells based on proton conductors (such as ) are not shown here, as the operating temperatures (400–600 °C) and steam contents (up to 10 vol%) reported for these proton‐conducting SOECs are very different from the ones based on conventional oxygen conductors (700–900 °C, 50 vol% or higher steam content). The cell with Pr 6 O 11 ‐SDC oxygen electrode achieved very high electrolysis performance, surpassing conventional electrode‐supported cells and all previous metal‐supported electrolysis cells.…”
Section: Resultsmentioning
confidence: 90%
“…Figure c compares the electrolysis performance of our optimized cells with those of oxygen‐conducting SOECs reported in the literature . Some recent advances of electrolysis cells based on proton conductors (such as ) are not shown here, as the operating temperatures (400–600 °C) and steam contents (up to 10 vol%) reported for these proton‐conducting SOECs are very different from the ones based on conventional oxygen conductors (700–900 °C, 50 vol% or higher steam content). The cell with Pr 6 O 11 ‐SDC oxygen electrode achieved very high electrolysis performance, surpassing conventional electrode‐supported cells and all previous metal‐supported electrolysis cells.…”
Section: Resultsmentioning
confidence: 90%
“…While the water splitting and oxygen reduction occur at the entire electrode surface, the improvement of mass transport is needed to make gas diffusion throughout electrode grains more necessary. The incorporation of the three-dimensional mesh-like PNC Kim et aI., 2016 38 Wang et aI., 2015 39 Chen et aI., 2015 40 Laguna-Bercero et aI., 2016 45 Ishihara et aI., 2016 46 Yang et aI., 2015 47 Peng et aI., 2010 41 Traversa et aI., 2015 42 Xie et aI., 2016 48 He et aI., 2017 49 Ding et aI., 2018 43 Kim et aI., 2018 44 Peng et aI., 2018 50 Liu et aI., 2018 51 Norby et aI., 2019 52 Haile et aI., 2019 53 electrode can make full use of the high porosity and active nanoparticles of nanofibers for superior performance. Our recent result has demonstrated that hydrogen production rate has been greatly improved by this self-architectured ultra porous layered perovskite PBSCF steam electrode 43 , e.g., 0.85 A cm −2 at 1.3 V and 600°C which was increased from regular electrode (0.55 A cm −2 ).…”
Section: Discussionmentioning
confidence: 99%
“…electrolyzers for high temperature water splitting and for co-electrolysis of CO2 and H2O [9][10][11][12].To split water, steam is supplied to the oxygen electrode of the PCEC and dry hydrogen is produced in the fuel electrode, so removal of steam from hydrogen is not needed, and electrochemical compression of H2 can be achieved [4,5]. For co-electrolysis of CO2 and H2O, the lower operating temperature of PCECs favors in-situ Fischer-Tropsch reactions [13], which are the rate-controlling reactions for co-electrolysis in solid oxide electrolyzer cells (SOEC) [14].The lower operating temperature further allows the use of less expensive interconnect and balance-of-plant (BoP) materials, resulting in lower manufacturing costs [15].Although protonic ceramic cell technology has shown great promise, most of the research and development efforts have focused only on the single cell level [1,2,4,7,[16][17][18][19]. Recently, researchers from South Korea demonstrated a scaled-up (5 × 5 cm 2 ) single protonic ceramic fuel cell that showed exciting high initial performance at intermediate temperatures [20].…”
mentioning
confidence: 99%
“…Although protonic ceramic cell technology has shown great promise, most of the research and development efforts have focused only on the single cell level [1,2,4,7,[16][17][18][19]. Recently, researchers from South Korea demonstrated a scaled-up (5 × 5 cm 2 ) single protonic ceramic fuel cell that showed exciting high initial performance at intermediate temperatures [20].…”
mentioning
confidence: 99%